Analisis Peduli Lingkungan Peserta Didik Kelas IV pada Mata Pelajaran IPAS Dalam P5 di SDN Anutapura - Moh Irfat; Andi Imrah dewi; Sinta Satrian Dewi Pendit; Sri Wahnyuni (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
This research aims to determine the implementation of environmental care attitudes of class IV students in science subjects at Anutapura Elementary School in P5. This research is a qualitative descriptive study with the research subjects being school principals, teachers and students. The object of this research is the implementation situation of character education that cares about the environment. This research uses data collection techniques in the form of observation, interviews and documentation. Data analysis by data reduction, data display, and drawing conclusions. Validity of data using triangulation techniques and sources. The results of the research show that overall, fourth grade students at Anutapura Elementary School have shown a very good attitude of caring for the environment and are in accordance with the values ​​contained in the Pancasila Student Profile in the science and sciences subject. Students not only understand the importance of protecting the environment, but also show active participation in various environmental conservation activities and are able to explain the impact of human behavior on nature. These students show a strong commitment to maintaining cleanliness, ecosystem diversity and environmental sustainability around them. Students have demonstrated behavior that reflects the character of Pancasila students, namely having faith, being devoted to God Almighty, having noble character, and caring and being responsible for the environment.